Psychological resilience in Olympic medal-winning coaches: A longitudinal qualitative study - Sarkar, M.; Hilton, N. K. (International Sport Coaching Journal, 2020)
The purpose of this study is, therefore, to explore psychological resilience in world-class coaches and how they develop resilience in athletes. In order to meet this objective, a longitudinal qualitative design will be adopted due to the dynamic and temporal nature of resilience. It is hoped that this study will offer an original and significant contribution to the resilience literature by providing a unique insight into how resilience unfolds over time in Olympic medal-winning swimming coaches. The results derived from data analysis procedures represent the collated interview responses from all five Olympic medal-winning coaches. The interview data yielded 14 higher order themes, which were categorized into the following three general dimensions: coach stressors, coach protective factors, and enhancing resilience in athletes. Drawing directly from the experiences of the participants across the two interviews, each general dimension will be illustrated by direct quotations from the transcripts, with the aim of providing an insight into how resilience unfolded over a 12-month swimming season in world-class coaches.